Reduction of L-phenylalanine in protein hydrolysates using L-phenylalanine ammonia-lyase from Rhodosporidium toruloides - Castañeda, María Teresita (2015)
L-Phenylalanine ammonia-lyase (PAL, EC 4.3.1.25) from Rhodosporidium toruloides was utilized to remove L-phenylalanine (L-Phe) from different commercial protein hydrolysates. A casein acid hydrolysate (CAH, L-Phe ~2.28 %) was employed as a model substrate. t-Cinnamic acid resulting from deamination of L-Phe was extracted, analyzed at λ = 290 nm, and used for PAL activity determination. Optimum reaction conditions, optimized using successive Doehlert design, were 35 mg mL⁻¹ of CAH and 800 mU mL⁻¹ of PAL, while temperature and pH were 42 °C and 8.7, respectively. Reaction kinetics of PAL with CAH was determined under optimized conditions. Then, removal of L-Phe from CAH was tested. Results showed that more than 92 % of initial L-Phe was eliminated. Similar results were obtained with other protein hydrolysates. These findings demonstrate that PAL is a useful biocatalyst for L-Phe removal from protein hydrolysates, which can be evaluated as potential ingredients in foodstuffs for PKU patients.